Nursing care during inter-hospital transport of the critically ill patient: scoping review - Fernandes, Elisabete; Infante, João; Mota, Mauro; Ribeiro, Olivério (Millenium - Journal of Education, Technologies, and Health, 2022)
Introduction: The inter-hospital transport of the critically ill patient is one of the most delicate care moments, during which it is necessary to maintain the support of vital functions, which begins with its preparation, until the moment the patient reaches the final destination. Objective: To identify the nurses' role and map the autonomous and/or interdependent interventions performed by nurses in the inter-hospital transport of critically ill patients. We also intend to identify the specific training that nurses have which enables them to perform inter-hospital transport. Methods: This Scoping Review followed the Joanna Briggs Institute’s methodology and intended to list published and unpublished studies on inter-hospital transport of critically ill patients, from 2001 in English, Portuguese, French and Spanish. The analysis of the studies was made by two independent reviewers. Results: The results of the research were grouped and explore the following data: author; year of publication; country; objectives of the studies; methods; population studied; training of nurses; administered interventions; nurses' skills and outcomes. Conclusion: The role of nurses in the inter-hospital transport of critically ill patients goes beyond the application of nursing techniques; their greatest contribution is related to the management of the clinical process, applying their technical knowledge, but also their personal skills are important to ensure the care and well-being of the patient.